PERAN KEPUASAN DALAM MEMEDIASI PENGARUH IMPLEMENTASI SERVICE EXCELLENCE TERHADAP LOYALITAS NASABAH PT.BANK MANDIRI, TBK KOTA BANYUWANGI - Utomo, Hardian Dwi; Irawan, Bambang; Yulisetiarini, Diah (BISMA: Jurnal Bisnis dan Manajemen, 2015)
Abstract: This study aims to identify and examine the role of customer satisfaction in mediating the effects of service excellence implementation on customer loyalty of PT Bank Mandiri Tbk, Banyuwangi. The sample consisted of 240 active customers. Structural Equation Modelling was used to test the hypothesis. Results show that: (a) ability, attitude, appearance, attention, action, and responsibility have positive effect on customer satisfaction and loyalty, (b) customer satisfaction has positive effect on customer loyalty, and (c) customer satisfaction mediates the effect of service excellence implementation on customer loyalty. Keywords: Ability, Atitude, Apperance, Attention, Action, Responsibility, Satisfaction, Loyality